Creencias de la comunidad educativa, del colegio Rodrigo Lara Bonilla i.e.d, ubicado en la cuidad de Bogotá, sobre la inclusión de estudiantes con discapacidad intelectual. (2018)
The inclusive education, has the aim to do effective the fundamental right that people with disabilities have to access to the education sistem with an excellent education. Likewise, it is imporant to hightlight that people with intelectual disabilities have been the central axis to promote the colombian’s education, distinguishing segregation, integration and inclution processes. On the other hand, this situation has permited a growing number of intelectual disable students, who are schooled. However, there is a porcentaje of these students, who are not and one of the reason is their disability